Life cycle assessment of Mahanarva andigena spittlebug on sugarcane seedlings - Valle Ramirez, Segundo Benedicto (2018)
The spittlebug Mahanarva andigena stands out as a pest of economic importance for the cultivation of sugar cane of Pastaza by its wide distribution in all the parishes in production. In order to implement studies of the biology of this pest insect associated with the crop, the duration of egg, nymph and adult stages on sugarcane seedlings was determined. In order to determine the first insect status, 90 x 15 mm Petri dishes were used in the Microbiology Laboratory of the State University of Amazonia at a temperature of 23 ± 1 oC and relative humidity of 80.20 ± 5.3%. Nymph and adult stages in greenhouse at a mean temperature of 23.81 ± 2.59 °C with relative humidity of 80.47 ± 8.36. For insect feeding in these states, POJ 93 sugar cane seedlings of 30 days of age were used in pots. The duration of the M. andigena embryo period was 19 ± 1.58 days, the nymph state was 46.5 ± 1.29 days and the adult state was 19 ± 1 day. The total life span of M. indigena in Pastaza was 84.5 ± 3.87 days.